An empirical study on the pricing strategies of hypermarkets in Singapore. - Koh, Wei Ling. (2008)
In this study, we examine the pricing behaviors of firms operating in the hypermarket sector in Singapore by investigating the relative price level set by retailers, the amount of price dispersion present in the market, and the price adjustment behaviors of retailers.